Tensile Properties And Water Absorption Of Wood Sawdust Filled Polypropylene Composites - Seow, Pek Ying (Universiti Sains Malaysia, 2018)
The biodegradability of natural fiber is one of the most promising aspects that related totheir incorporation in polymeric materials. The aim of this project is to compare the performance of treated and untreated wood sawdust filled PP composites with different fiber loading which are 2.5 wt%, 5 wt%, 7.5 wt% and 10 wt%. Comparison on the properties of wood sawdust composites with various types of natural fiber and filler composites was carried out. The wood sawdust was treated with NaOH solution. Sawdust filled PP composites were compounded by using Thermo Haake Polydrive internal mixer followed by compression molding. The tensile properties, morphology, chemical functional group analysis and water absorption of composites were analysed. In general, the treated sawdust filled PP composites exhibit 7.1% and 4.1% improvement in tensile strength and tensile modulus at 2.5 wt% and 7.5 wt%, respectively than those untreated sawdust filled PP. Based on the morphology observation, rougher surface introduced by the alkaline treatment increases the surface area of contact of the fiber and matrix by improving the interfacial bonding. Furthermore, treated sawdust filled PP composites show 7.8% lower water absorption as compared with untreated sawdust filled PP composites. Besides, the tensile properties such as tensile strength and Young’s modulus of various types of natural fibers were compared. In general, coconut shell shows the highest tensile properties compared to those composites with wood sawdust, kenaf fiber and egg shell filled PP composites. In conclusion, treated sawdust composites exhibit a positive effect on PP composites properties compared to the untreated sawdust composites.